Magnetic field induced alignment of graphene nanoplatelets in epoxy resin to develop model nanocomposite - Tiwari A.; Panda S.K. (My University, 2025)
In this work, a mathematical model is developed to optimize the alignment parameters of Graphene Nanoplatelets (GNP) and Fe3O4-GNP applying a weak DC magnetic field (0.05 T), considering rotation, translation, migration, and slackening mechanisms of the nanoparticle in the epoxy. The characteristic magnetic, viscosity and hydrodynamic parameters required by the mathematic model are determined experimentally by synthesizing the magnetite ferric oxide (Fe3O4) and attaching them to GNP to increase its magnetic susceptibility. A highly aligned Fe3O4-GNP nanocomposite is fabricated at 0.05 T magnetic field and 40 Pa-s dynamic viscosity of epoxy, as evident from the optical image analysis. The mass magnetic susceptibility for the nanoparticles are determined at different magnetic field. Time needed for the alignment process at 0.05 T and viscosity range 10–50 Pa-s are compared among the rotation, chaining, migration and the slackening phenomena. The procedure demonstrated to prepare fully cured nanocomposite with aligned Fe3O4-GNP can be used in advanced structures. © The Author(s) 2023.